(untitled) (Rudarsko-geološko-naftni zbornik, 2024)
Mt. Medvednica belongs to the western part of the Neogene rift-type North Croatian Basin that occupies the south-western Pannonian Basin System. The Lower to Middle Miocene continental to marine sedimentary complex was studied on Mt. Medvednica in order to interpret the early syn-rift depositional environment and reconstruct palaeogeography of the North Croatian Basin. Based on facies analysis, deposits are grouped into 16 facies based on their lithological characteristics. Six of the facies belong to the alluvial environment that is characterized by coarse-grained bedload siliciclastics. Nine facies are of lacustrine origin. They comprise: a) limestone of shallow lake carbonate bench with silty coal of vegetated marsh, b) deep lake and prodelta marl with sand and conglomerate intercalations deposited by gravity flows, and c) coarse-grained Gilbert-type delta conglomerate. The lacustrine deposits compose a transgressive-regressive sequence. The studied succession ends by facies of calcareous silt intercalated by conglomerates. These deposits belong to the marine offshore to prodelta as the consequence of establishment of the connection to the sea. The deposition was strongly controlled by allogenic factors, such as synsedimentary tectonics, climate, eustatic sea level changes and explosive volcanic activity. The alluvial deposits of Mt. Medvednica are the oldest syn-rift deposits and belong to the large alluvial plain that probably covered the entire North Croatian Basin in the Ottnangian and the Karpatian. These deposits are overlain by the lower Badenian lacustrine deposits, but the question of the existence of one large or several small lakes in the early Badenian North Croatian Basin remains open.